Prevalence Of Cardiorespiratory Impairment In Post Stroke Survivors - Mangrulkar, Vaishnav Chandrashekhar; Devi, T. Poovishnu; Kamble, Maitreyi (Journal of Neonatal Surgery, 2025)
Background: Stroke, caused by a blockage or rupture in brain vessels, results in sudden brain dysfunction and is a leading cause of long-term disability. Reduced activity following a stroke decreases cardiorespiratory fitness (CRF), impairs mobility, and increases the risk of future strokes and heart problems. All strokes, including ischemic and haemorrhages, raise vascular risk. Managing blood pressure, obesity, smoking, and glucose is critical for recovery and prevention. Methods: This study is observational, and was conducted on sixty four people suffering from cardiorespiratory impairment in post stroke. A questionnaire was provided to the participants. the result were analysed according to the interpretation of questionnaire. Result: A simple random survey of 64 post-stroke survivors revealed that 71.8% had signs of cardiorespiratory impairment, indicating a significant concern in this population. Conclusion: Cardiorespiratory impairment is a common concern among post-stroke survivors, resulting in reduced function, a lower quality of life, and an increased risk of recurring heart problems. Based on this, 64 participants with such impairments were evaluated using a questionnaire.